The growth trend of planted trees (Pinus sylvestris L.) in the early stage of plantation establishment - G, Batsaikhan; J, Tsogtbaatar; S, Gerelbaatar (Proceedings of the Mongolian Academy of Sciences, 2018)
This study examined the growth of planted Scots Pine trees of different ages growing in the Tujyin Nars National park, located in Selenge aimag in the north of Mongolia. A total of seven, 50 x 20 m (0.1 ha) sized sample plots were established using a completely randomized sampling design. The tree growth monitoring was carried out between 2003 and 2017, by an annual repeated measurement at the end of each growing season. The total height, annual height increment and diameter at breast height were measured at sample plots and tree samples were taken for laboratory analysis. For statistical analysis, a One-way analysis of variance (One-way ANOVA) and F-test were applied. Our findings showed that the annual height (F=15.21, P<0.0001) and radial increments (F=15.76, P<0.0001) varied among plantations commensurate to their age. In our study, the highest height (46.5±6.1 cm) and radial (4.1±0.8 mm) increment were occurred in 12 and 10 years old plantations. Therefore, a strong positive correlation (r=0.99) between tree increment and plantation age was observed in plantations below 12 years of age. After this age, increment values were relatively stable, which tended to gradually decrease with plantation age. Our findings confirm that initial planting design leads to overcrowding with plantation age; therefore, implementation of a thinning practice is necessary after a plantation reaches 12 years of age. The ever-decreasing trend of both radial and height increments in plantations beyond 12-years of age supports the importance of thinning as a practice to reduce competition and to support the growth of remaining trees in older plantations.